IMPLEMENTATION OF LINIER REGRESSIONUSING THE JSN-SR04T SENSOR FOR THE MONITORING WATER LEVEL IN WATER TANKS THROUGH ANTARES PLATFORM - Garnis Hasna Iftinan Apsari; Sigit Pramono; Nur Afifah Zen (Journal of Electronic and Electrical Power Applications, 2022)
Its use as a water storage location means that it is not uncommon for the water tank to overflow if the water level exceeds the maximum limit. One of the airtight ultrasonic sensors is the JSN-SR04T ultrasonic sensor for measuring water levels. However, this sensor has a weakness in the measurement reading that is less accurate. One way to improve the accuracy of this sensor's reading is to use the Linear Regression method. The purpose of this research is to test the accuracy of sensor measurement and the effect of linear regression implementation. The platform used in this research is Antares which is used for storing measurement data results. The results of the sensor measurement test show that the sensor is less accurate in measurement, after being implemented with the linear regression method the measurement results are approaching accurate but there is still a slight difference. The linear regression method is able to improve the accuracy of measurement data results better than before using linear regression.